Designing luxury experience - Vadim Grigorian; Francine Espinoza Petersen (European School of Management and Technology (ESMT), 2014)
In luxury brand management, experiences are essential. However, most of what we know about designing customer experiences originates from work developed with and/or for mass brands. Luxury brands are conceptually different and require a specific approach to brand management. Using a grounded theory approach, we present a framework consisting of seven principles to design luxury experience. Our research suggests that to create a true luxury experience brands should go beyond traditional frameworks of brand management. By compiling best practices and the commonalities amongst the interviewed companies' most successful efforts to create a luxury experience, the framework can help brands to implement a trading-up strategy: Luxury brands can enhance their desirability by offering a true luxury experience and non-luxury brands can adopt principles of luxury experience and become life-style brands.
urn:nbn:de:101:1-2014090212283
Keywords: 650; Brand management; luxury brands; luxury marketing; emotions; customer experience; experience design; luxury consumption